2019
DOI: 10.3390/app9102041
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fish Density and Echo Strength Distribution Recorded by Two Generations of Single Beam Echo Sounders

Abstract: Hydroacoustic acquisition was performed by means of two different single beam systems, the Simradmodel EK15 from 2015 and the Simrad model EY-M from the 1980s to explore potential differences of fish density and target strength (TS) distribution between EK15 and EY-M-based estimates. The oligotrophic Lake Storsjøen (48 km2) with steep shores, was chosen for the survey. The pelagic fish stock is dominated by whitefish (Coregonus lavaretus L.), and, recently, illegally stocked smelt (Osmerus eperlanus L.), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The pelagic fish density was estimated irregularly over 34 years from 1985 with a single beam echosounder SIMRAD EY-M [ 57 ] in the period 1985–2014, and from 2015 to 2018, the single beam SIMRAD EK15 device [ 58 ] was used. The two systems were compared in a survey in Lake Storsjøen in Rendalen in 2016, and the results proved comparable [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pelagic fish density was estimated irregularly over 34 years from 1985 with a single beam echosounder SIMRAD EY-M [ 57 ] in the period 1985–2014, and from 2015 to 2018, the single beam SIMRAD EK15 device [ 58 ] was used. The two systems were compared in a survey in Lake Storsjøen in Rendalen in 2016, and the results proved comparable [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sampling was done along transects crossing from shore to shore (see Linløkken et al [ 8 , 30 ]), and the degree of coverage S (=Pooled recorded distance/(Lake area) 0.5 ) was larger than 3, as recommended by Aglen [ 61 ], except in three lakes, Lake Hemnessjøen (S = 2.55), Lake Gopollen (S = 2.0), and Lake Furusjøen (S = 0.6), where less than 30% of the surface covered depth >10 m. Fish biomass was calculated by means of the relationship between fish length ( L ) and weight ( W ), expressed as W = a • L b [ 62 ] with species specific parameters a and b. Depending on the species present in the lake, parameters of smelt (a = 1.7 × 10 −6 , b = 3.19, from Storsjøen in Rendalen, unpublished ) were used for fish smaller than 15 cm, parameters of vendace (a = 24.0 × 10 −6 , b = 2.26, from Lake Osensjøen [ 8 ]) were used for fish smaller than 25 cm, and otherwise parameters of whitefish (a = 15.2 × 10 −6 , b = 2.89, from Lake Osensjøen [ 8 ]) or of Arctic charr (a = 6.25 × 10 −6 , b = 3.05, from Lake Sølensjøen [ 54 ]) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid advances in the miniaturization of acoustic sensors (transducers) and the improvement of batteries and computers allow them to be mounted on various mobile platforms, such as gliders and AUVs (Hine et al, 2009;Moline et al, 2015) and buoys (Godo and Totland, 1999;Brehmer et al, 2018), thus rendering this sensing technology cost-effective both in hardware and in deployment compared to traditional shipboard transducers. In the last decade, a new cost-effective multipurpose scientific echosounder, the Simrad EK15, was designed and validated (Betanzos et al, 2016;Linløkken et al, 2019). Another major development in cost-effective acoustic sensing is the scientific wide band echosounders (Demer et al, 2017) which use a wide band transceiver (WBT) to replace the general purpose transceiver (GPT) that is used for narrow-bandwidth echosounders, e.g., the WBT Miniature wideband transceiver (WBT Mini) (Benoit-Bird et al, 2018), wide-band autonomous transceiver (WBAT), and WBT Tube Subsea transceiver (WBT Tube) (Lavery et al, 2017).…”
Section: Underwater Bio-acousticsmentioning
confidence: 99%
“…Linløkken et al [7] explored and reported acceptable differences of fish density and Target Strength distribution estimates between two ingle beam systems, EK15 and EY-M, in the paper "Comparing Fish Density and Echo Strength Distribution Recorded by Two Generations of Single Beam Echo Sounders". They showed that the measurement site, the oligotrophic Lake Storsjøen (48 km 2 ), has nurtured the introduced smelt population since 2013, by using the dramatic increase of density of TS = −46 to −44 dB echoes (>10 cm) between 2013 and 2016.…”
Section: Acoustic Biomass Estimationmentioning
confidence: 99%